Microalbuminaria in hypertension: a review - Bhattarai, Mahesh; Bhandari, Buna (Journal of Nobel Medical College, 2012)
Microalbuminuria appears early in the natural history of kidney disease. Hypertension accelerates the progressive increase in albuminuria and decline in glomerular filtration rate, albuminuria is the most important risk for progressive kidney injury. Greater urinary albumin excretion is due to increased glomerular hydrostatic pressure and increased permselectivity of the glomerular basement membrane. Reduction in albuminuria is protective for the development of complication, Angiotensin converting enzyme inhibitor leads to larger decrease in albuminuria when compared to other antihypertensive drugs. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7292 Journal of Nobel Medical College (2012), Vol.1 No.2 p.1-10